Ectomycorrhizal identification in environmental samples of tree roots by Fourier-transform infrared (FTIR) spectroscopy - Pena, Rodica; Lang, Christa; Naumann, Annette; Polle, Andrea (Frontiers in Plant Science, 2014)
Roots of forest trees are associated with various ectomycorrhizal (ECM) fungal species that are involved in nutrient exchange between host plant and the soil compartment. The identification of ECM fungi in small environmental samples is difficult. The present study tested the feasibility of attenuated total reflection Fourier-transform infrared (ATR-FTIR) spectroscopy followed by hierarchical cluster analysis (HCA) to discriminate in situ collected ECM fungal species. Root tips colonized by distinct ECM fungal species, i.e., Amanita rubescens, Cenococcum geophilum, Lactarius subdulcis, Russula ochroleuca, and Xerocomus pruinatus were collected in mono-specific beech (Fagus sylvatica) and mixed deciduous forests in different geographic areas to investigate the environmental variability of the ECM FTIR signatures. A clear HCA discrimination was obtained for ECM fungal species independent of individual provenance. Environmental variability neither limited the discrimination between fungal species nor provided sufficient resolution to discern species sub-clusters for different sites. However, the de-convoluted FTIR spectra contained site-related spectral information for fungi with wide nutrient ranges, but not for Lactarius subdulcis, a fungus residing only in the litter layer. Specific markers for distinct ECM were identified in spectral regions associated with carbohydrates (i.e. mannans), lipids, and secondary protein structures. The present results support that FTIR spectroscopy coupled with multivariate analysis is a reliable and fast method to identify ECM fungal species in minute environmental samples. Moreover, our data suggest that the FTIR spectral signatures contain information on physiological and functional traits of ECM fungi.